Gamification and Student Well-being: Exploring the Psychological Impact of Game-Based Learning - Adiyati Fathu Roshonah; Nong Chai; Rustiyana Rustiyana; Dito Anurogo (Yayasan Adra Karima Hubbi, 2025)
Background. The increasing integration of digital learning environments has accelerated the adoption of gamification as a pedagogical approach to enhance engagement and student well-being. Contemporary education faces growing challenges related to academic stress, low motivation, and diminished emotional resilience among learners. Purpose. This research investigates the psychological effects of game-based learning, focusing on how gamification elements such as rewards, competition, collaboration, and feedback affect students’ emotional states, motivation, and perceived well-being. Method. The study aims to bridge the gap between cognitive engagement and affective learning outcomes by empirically examining the psychological dynamics fostered by gamified educational experiences. A mixed-method design was employed, combining quantitative data from 320 undergraduate students across four universities and qualitative interviews with 24 participants. Results. Instruments included validated scales measuring intrinsic motivation, emotional engagement, and academic well-being. Data analysis was conducted using structural equation modeling (SEM) to identify causal relationships between gamification components and psychological indicators. Conclusion. The study concludes that gamification serves not only as a motivational tool but also as a psychological support mechanism in learning environments.